Microparticles and Fibrinolysis - Vallier, Loris; Cointe, Sylvie; Lacroix, Romaric; Bonifay, Amandine; Judicone, Coralie; Dignat-George, Françoise; Kwaan, Hau C. (Seminars in Thrombosis and Hemostasis, 2017)
Microparticles (MPs) are submicronic vesicles which are formed by budding of the cellular membrane of virtually any cell type in response to cell activation or apoptosis. Both circulating MPs and MPs generated within tissues harbor molecules with a large repertoire of biological activities and transfer material to target cells. Depending on their cellular origin, the stimuli triggering their formation, or their localization, they may participate in the maintenance of organ or vascular homeostasis as well as inducing dysfunction. MPs have mostly been described as having procoagulant properties. However, the fact that some MP subsets are able to efficiently generate plasmin suggests that the role of MPs in hemostasis is more complex than initially thought. In this review, we summarize key findings showing that MPs provide a heterogeneous catalytic surface for plasmin generation, according to their cellular origin. We further address the specific features of the MP-dependent fibrinolytic system. Potential consequences of this MP-associated fibrinolytic activity in pathology are illustrated in cancer.
Keywords: extracellular vesicles; cancer; fibrinolysis; hemostasis; microparticles